Plasma physics and control studies planned in JT-60SA for ITER and DEMO operations and risk mitigation. (1st May 2022) - Yoshida, M; Giruzzi, G; Aiba, N; Artaud, J F; Ayllon-Guerola, J; Balbinot, L; Beeke, O; Belonohy, E; Bettini, P; Bin, W; Bierwage, A; Bolzonella, T; et al.
Abstract: A large superconducting machine, JT-60SA has been constructed to provide major contributions to the ITER program and DEMO design. For the success of the ITER project and fusion reactor, understanding and development of plasma controllability in ITER and DEMO relevant higher beta regimes are essential. JT-60SA has focused the program on the plasma controllability for scenario development and risk mitigation in ITER as well as on investigating DEMO relevant regimes. This paper summarizes the high research priorities and strategy for the JT-60SA project. Recent works on simulation studies to prepare the plasma physics and control experiments are presented, such as plasma breakdown and equilibrium controls, hybrid and steady-state scenario development, and risk mitigation techniques. Contributions of JT-60SA to ITER and DEMO have been clarified through those studies.